In vitro antimicrobial interactions and in vivo synergy of ceftriaxone and streptomycin against Haemophilus ducreyi. - Roy, Josée. (University of Ottawa (Canada), 1996)
Haemophilus ducreyi is the etiologic agent of chancroid, a classic sexually transmitted genital ulcer disease. In endemic areas, HIV and chancroid interact in a complex, bidirectional epidemiology and biologic manner so as to amplify the prevalence of each other. Chancroid outbreaks can be controlled with the help of efficacious antibiotic treatment. Single doses of ceftriaxone, azithromycin and fleroxacin have been used successfully. However, because of HIV associated immune disease, an unacceptable failure rate of over 20% has been observed with concurrent HIV infections, and this, in the absence of H. ducreyi drug resistance. In this study, two-drug combinations of ceftriaxone, streptomycin, azithromycin and rifabutin were assayed in vitro by the checkerboard agar dilution technique for their activity against H. ducreyi strains proven susceptible by limiting agar dilution minimum inhibitory concentration determination. We conclude that a supra-additive effect observed between ceftriaxone and streptomycin in vitro by the checkerboard technique was corroborated by a synergistic effect observed between the same antimicrobial agents in the temperature-dependent rabbit model of infection. This combination may be evaluated as a single-dose in the treatment of chancroid in all patients, particularly those with HIV coinfection.
Keywords: Biology, Microbiology.